2015
DOI: 10.1111/joic.12226
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Access PCI in a Default Radial Center Identifies High‐Risk Patients With Poor Outcomes

Abstract: In a default radial PCI center 10% of patients undergo PCI via the femoral artery. These patients have high baseline bleeding risk and undergo complex interventions. As a result the incidence of major bleeding, transfusion and death are high. Alternative strategies are required to optimize outcomes in this select group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Since bleeding requiring blood transfusion after PCI is closely associated with mortality, 22,23) it would be of utmost importance to prevent bleeding after PCI. Our multivariate logistic regression analysis included multiple clinical risk factors for bleeding after PCI such as age, 13,14) sex, 5,15) body mass index, 14) sheath size, 16) hemoglobin, 14,17) chronic renal failure on HD, 14,18) and anticoagulation therapy; 14) however, protamine use was only significantly associated with bleeding requiring blood transfusion in our multivariate analysis. Furthermore, only protamine use was a modifiable factor without sacrificing safety, while discontinuing anticoagulation or reducing sheath size would pose a potential risk for pa-SAFETY OF REVERSING ANTICOAGULATION Data were expressed as mean ± SD or numbers (percentages).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since bleeding requiring blood transfusion after PCI is closely associated with mortality, 22,23) it would be of utmost importance to prevent bleeding after PCI. Our multivariate logistic regression analysis included multiple clinical risk factors for bleeding after PCI such as age, 13,14) sex, 5,15) body mass index, 14) sheath size, 16) hemoglobin, 14,17) chronic renal failure on HD, 14,18) and anticoagulation therapy; 14) however, protamine use was only significantly associated with bleeding requiring blood transfusion in our multivariate analysis. Furthermore, only protamine use was a modifiable factor without sacrificing safety, while discontinuing anticoagulation or reducing sheath size would pose a potential risk for pa-SAFETY OF REVERSING ANTICOAGULATION Data were expressed as mean ± SD or numbers (percentages).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, bleeding requiring blood transfusion was adopted as a dependent variable. The use of protamine and clinically proven risk factors for blood transfusion following PCI such as age, 13,14) sex, 5,15) body mass index, 14) sheath size, 16) hemoglobin, 14,17) chronic renal failure on HD, 14,18) and anticoagulation therapy 14) were used as independent variables. In multivariate logistic regression analysis, the backward stepwise (likelihood ratio) method was used because the number of events (bleeding requiring blood transfusion) was only four.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the findings of this study could represent the fact that when default radial operators use the femoral approach, patients tend to be much sicker. 12 The authors accounted for these changes in patient population by controlling for a variety of potential confounders, including cardiogenic shock, and the results were consistent in those analyses. Although the authors adjusted for cardiogenic shock and similar findings were seen in the subgroup of patients who did not have cardiogenic shock, all observational studies are potentially subject to unmeasured confounding.…”
Section: See Article By Hulme Et Almentioning
confidence: 71%
“…11 In addition, the population for whom they are likely to offer TRA changes to incorporate higher risk patients. 12 This is important because these higher risk patients, such as those with acute coronary syndrome who are being treated with potent antiplatelet and anticoagulants, and those undergoing procedures are patients who showed particular benefit in the RIVAL and MATRIX trials. Thus, the use of strategies to avoid bleeding in those patients who are at the highest risk of adverse events and death may be the key factor that is driving the benefit of TRA.…”
Section: See Article By Hulme Et Almentioning
confidence: 99%
“…Previous work has suggested that patients undergoing femoral procedures in predominantly radial centers tend to be older, more hemodynamically unstable, and have a greater prevalence of adverse procedural risk factors, such as renal failure, poor left ventricular function, and at higher bleeding risk 12,13,31 as defined by the Mehran bleeding risk score. 32 Our work shows that nearly 60% of centers in the United Kingdom (53 of 92 centers) have transitioned to become predominantly radial centers with more than two-third of their PCI case mix being undertaken through the TRA approach.…”
Section: Discussionmentioning
confidence: 99%